2009
DOI: 10.3109/01942630903245994
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Adult-Oriented Health Care: Perspectives of Youth and Adults with Complex Physical Disabilities

Abstract: The challenges of clinical transition were universal. More extensive information and support is needed during transition to ensure an efficient move to appropriate adult-oriented health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 27 publications
0
59
0
Order By: Relevance
“…The lack of another, better, alternative had them accepting less. All participants identified challenges in transition, including: lack of access to health care; lack of professionals' knowledge; lack of information and uncertainty regarding the transition process (Young et al, 2009). Providing interventions that decrease the negative feelings associated with transition (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…The lack of another, better, alternative had them accepting less. All participants identified challenges in transition, including: lack of access to health care; lack of professionals' knowledge; lack of information and uncertainty regarding the transition process (Young et al, 2009). Providing interventions that decrease the negative feelings associated with transition (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…8 Young et al found that a common barrier to transition in Canada for individuals who suffer from SB, cerebral palsy, and acquired brain injury was an inability to access adult physician specialists, which is an unforeseen finding due to Canada's government-funded healthcare system. 13 It was determined that 7/9 pediatric urologists from the province of Ontario do not provide ongoing care to SB patients after the age of 18. Koyle et al have proposed that the alternate funding plan in Ontario potentially hampers provider continuity and suggested a culture change was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The rational for classifying all YSHCN in the same category was to prevent gaps and duplication of services, which became apparent in the second half of the century until a unified definition was developed which would help in the allocation of resources (McPherson et al, 1998). Furthermore, YSHCN face similar barriers that can prevent successful transition to adult care (Betz, 2007;Reiss, Gibson, & Walker, 2005;Young et al, 2009). Although YSHCN have many different diagnoses, they all would need to be offered the same services for transition (AAP, AAFP & ACP, 2011).…”
Section: Gaps In the Literaturementioning
confidence: 97%